2013
DOI: 10.1136/bmjopen-2013-002889
|View full text |Cite
|
Sign up to set email alerts
|

What can qualitative research do for randomised controlled trials? A systematic mapping review

Abstract: ObjectiveTo develop an empirically based framework of the aspects of randomised controlled trials addressed by qualitative research.DesignSystematic mapping review of qualitative research undertaken with randomised controlled trials and published in peer-reviewed journals.Data sourcesMEDLINE, PreMEDLINE, EMBASE, the Cochrane Library, Health Technology Assessment, PsycINFO, CINAHL, British Nursing Index, Social Sciences Citation Index and ASSIA.Eligibility criteriaArticles reporting qualitative research underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
316
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(327 citation statements)
references
References 37 publications
(19 reference statements)
1
316
1
1
Order By: Relevance
“…Previous studies have indicated that a sample of approximately 40 trial participants would be sufficient to address these aims from the point of view of service users. 60 All case managers working in York and Leeds at the time of the pilot phase were recruited for interview by invitation through the local trial co-ordinators.…”
Section: Samplingmentioning
confidence: 99%
“…Previous studies have indicated that a sample of approximately 40 trial participants would be sufficient to address these aims from the point of view of service users. 60 All case managers working in York and Leeds at the time of the pilot phase were recruited for interview by invitation through the local trial co-ordinators.…”
Section: Samplingmentioning
confidence: 99%
“…[8][9][10] An understanding of clinicians' views and experiences of using different interventions in practice, in relation to their patients, can help identify the 'active ingredients' of a complex intervention, explore the feasibility, acceptability, and transferability of the intervention, and thus help inform refinement and implementation. Exploring whether an intervention that has been shown to be effective across multiple European countries has different levels of acceptability or is used in different ways in different countries may provide opportunities for changing clinicians' behaviour on a wider scale without having to repeat clinical trials in each new setting.…”
Section: Introductionmentioning
confidence: 99%
“…260,261 In the BEEP trial, linked, longitudinal, qualitative interviews explored participants' experiences of treatment, their views of the acceptability of their treatment, the impact of the interventions on participants' exercise and general physical activity behaviour, and explanations for change in knee symptoms and exercise behaviour over time. The topic guides (see Appendix 3) included questions that explored participants' views of their physiotherapy treatment, how they got on with their exercise programme and what factors they felt helped or hindered them to adhere to the exercises following the end of their treatment contact with the physiotherapist and approximately 12-18 months later.…”
Section: Linked Qualitative Interviewsmentioning
confidence: 99%